Predictors of assertive behaviors among a sample of first-year Tunisian medical students. Issue 1 (31st December 2022) - Ben Cherifa, Dorra; Saguem, Bochra Nourhene; Chelbi, Souad; Braham, Amel; Ben Nasr, Selma; Ben Saad, Helmi
ABSTRACT: Assertiveness is a constructive interpersonal behavior alternative to manipulation and aggression. Medical students (MSs) have daily interpersonal interactions with colleagues, patients and families. Yet, communication deficiencies due to hesitancy to speak-up assertively lead to adverse patient outcomes. This study aimed to assess levels of assertive behaviors (ABs), and to determine its predictors within a sample of first-year Tunisian MSs. This was a cross-sectional survey including 125 first-year MSs from Tunisia. ABs were measured by the Rathus assertiveness scale. Potential independent predictors of AB were evaluated using the following questionnaires: Rosenberg self-esteem scale, interpersonal communication skills inventory short-form-36quality of life questionnaire, and general health questionnaire. In addition, some MSs' characteristics were considered ( eg ; age, sex, living with family, assertiveness training, community work, personal medical field choice, smoking, and alcohol use). Univariate and multivariate analyses were performed. Among the 309 MSs, 125 (40.45%) responded to the survey. AB were found in 36.8% of MSs. Multiple linear regression models revealed that self-esteem global scores, sending clear messages, anxiety/depression and male sex were accountable for 31% in AB scores variance. Targeting self-esteem and interpersonal communication skills (sending clear messages) and identifying subgroups of students with anxiety/depression state would influence ABs.